Tooth loss leads to reduced nutrient intake in middle-aged and older Japanese individuals - Takayuki Kosaka; Momoyo Kida (Komiyama Printing Co. Ltd, 2019)
Abstract Reductions in masticatory function as a result of tooth loss have a negative impact on nutrient intake, decreasing general health. In addition, studies have reported an association between lower socioeconomic status (SES) and both higher numbers of lost teeth and worse nutrient intake status. Nakamura et al. conducted a study to clarify the relationship between number of teeth and nutrient intake status in their paper "Having few remaining teeth is associated with a low nutrient intake and low serum albumin levels in middle-aged and older Japanese individuals: Findings from the NIPPON DATA", evaluating not only data obtained from a household-based dietary survey but also serum albumin levels as a nutritional biomarker. Importantly, the present study also took into account the individual SES of subjects in the analysis of number of teeth and nutrient intake. The present results show that the trend for poorer nutrient intake with lower number of teeth is more marked among individuals with low SES. It is therefore essential that individual SES is taken into account in efforts to improve nutrient intake and thus contribute to general health through oral health.